Effect of age and magnesium supply on the free radical and anti-oxidant content of plants - Kiss, Sándor A. (Acta Biologica Szegediensis, 2003)
The scientific literature signs that the shortage of magnesium may increase the free radical content in the animal and human tissues, but nothing can be kown about a similar effect in the plants. This is why we decided to research the plant tissues to know how the radical content and the concentration of antioxidants which may eliminate the free radicals. We have researched the wheat (Triticum aestivum var. GK Pinka), maize (Zea mays var. Furio) and table beet (Beta vulgaris var. Rubra). We measured the concentrations in the coleoptyle of wheat and maize and in the roots of table beet. On the basis of our measurements we may conclude that the increase of magnesium concentration in the nutrient solution does decrease the radical content (HO•, LPO) and the activity of antioxidants. It is known, that the production of free radicals does increase as the uncoupling of oxidative phosphorilation is increasing according to its measure. Nevertheless the reduction of concentration of magnesium increases the measure of uncoupling of oxidative phosphorilation and the production of free radicals. On the basis of these effects one can understand why the radical content is lower after the addition magnesium ions into the nutrient solution. The decrease of activity of activity of GSH, catalase and FRAP-value may be understood also: the real cause is the fact that the promoter free radicals needed to the “de novo synthesis” have decreased. The last conclusion may be the next: the magnesium does influence the of free radicals and antioxidants in the plant tissues.